Differences between bone mineral density, lean and fat mass of HIV-positive and HIV-negative black women. Issue 2 (4th May 2019) - Ellis, C; Kruger, HS; Ukegbu, P; Kruger, IM; Viljoen, M; Kruger, MC
Abstract : Objectives: To investigate the differences between bone mineral density (BMD), lean and fat mass of human immunodeficiency virus (HIV-) positive and HIV-negative black women and to investigate factors associated with low BMD. Methods: Case-control study of black women ( n = 565) aged 29–65 years from Potchefstroom, North West province, South Africa, based on secondary analysis of data. Total BMD, left femur neck of the hip (LFN BMD), spine BMD, total fat, fat-free tissue mass and percentage body fat (%BF) were measured by dual-energy X-ray absorptiometry. Results: HIV-negative women had significantly higher median BMD, %BF, appendicular skeletal mass (ASM), ASM index, body mass index (BMI) and waist circumference than HIV-positive women. When the groups were matched for age and BMI, only spine BMD was marginally lower in HIV-positive women. In the total group, age, smoking and HIV status were associated with lower BMD, while calcium intake was positively associated with BMD. Similar variables were associated with BMD in HIV-negative women, while age and educational status were associated with BMD in HIV-positive women. Conclusion: Low BMD was more common among HIV-positive than HIV-negative women. Older HIV-positive women with low educational status are particularly at risk.